Domestic recreational economic value of Kilim Karst Geoforest Park, Langkawi - Zameli, Nurul Hikmah; Mohammad Afandi, Syamsul Herman; Samdin, Zaiton; Shuib, Ahmad (2013)
The need for recreation and travel among domestic tourists nowadays is increasing. Kilim Karst Geoforest Park (KKGP), Langkawi is one of a tourism sites in rural area which has emerge to be a popular tourist destination. A quantitative measure of economic value have been conducted, in which, Travel Cost Method (TCM) is employed to attain the value. The aim for this study is to assess the domestic economic value of KKGP. A total of 300 of domestic respondents were interview by using a structured questionnaire in KKGP. The findings show that there are more female tourists (56%). Most of the tourists are in the range of 41-55 years old (29.3%) age group. The highest (34.6%) percentages of tourists are at Diploma/Professional certificate level. Service related work is found to be the highest (24.1%) type of profession. There are seven independent variables included in the multiple regression model in determining the factors influencing visits to KKGP. Only two factors are found to be significant at 5% confidence level, namely travel cost to KKGP and alternative cost. The consumer surplus is estimated at RM3,298.60 per year at zero cost. The estimated average consumer surplus is RM69.10 /person/visit/year. Thus, the recreational economic value for KKGP is estimated at RM8,107, 977.40 for the year 2011. The findings in this study provide information for management in KKGP to justify its development and ensure a more efficient allocation of resources.